Viscosupplementation in prevention and treatment of the degenerative joint disease - Kotela, Andrzej; Sarzyńska, Sylwia; Woźniak, Maria; Łęgosz, Paweł; Starczyńska, Małgorzata; Kotela, Ireneusz (Medical Studies/Studia Medyczne, 2015)
Osteoarthritis (OA) is one of the most common musculoskeletal disorders. It limits patients’ functionality and life satisfaction significantly. Although there are numerous types of therapy, the success rate of conservative treatment is limited, and it is often necessary to introduce surgical treatment. Therefore, new effective methods of therapy for OA are being tested and submitted. Endogenous hyaluronic acid (HA) is a natural ingredient of many tissues in the human organism, including synovial fluid. Viscosupplementation with the usage of HA is a relatively new method for treating degenerative joint changes. By virtue of its good safety profile and simplicity of application, it is increasingly used as an alternative or addition to classic conservative treatment. In this work, we attempted to summarise the current state of knowledge of HA usage in OA treatment based on literature.